Geology from Engineering, Urban or Otherwise - Karrow, Paul (Géographie physique et Quaternaire, 1988)
ABSTRACTExhortations of the mid-nineteenth century to take advantage of construction activities as sources of geological information have been paid heed only occasionally. While some advantage has been taken of information from engineering activity, most is unrecorded geologically. Geological study of urban areas is complicated by many difficulties and comprehensive treatment requires a permanent staff with appropriate experience. Even though geological data have clearly demonstrable practical use in better use of land resources, urban geology should embrace both practical and curiousity-based research. Thus far, opportunities to gain enormous amounts of information of great practical and scientific value have been commonly ignored. Toronto is Canada's largest and geologically most famous city. The fame is based on its unique Quaternary stratigraphy, which includes lllinoian, Sangamonian, and Wisconsinan deposits, many of which are fossiliferous. Tragic losses of important information about its Quaternary history occur nearly continuously as large scale surface mining continues and little record of the temporary exposures is kept.